The value of atrial electromechanical delay in predicting atrial fibrillation development after coronary artery bypass surgery. Issue 1 (6th December 2021) - Taner, Temmuz; Pala, Arda Aybars; Camci, Sencer; Turk, Tamer; Ari, Hasan
Abstract: Objective: Predicting postoperative atrial fibrillation (PoAF) in the preoperative period will provide a serious advantage in preventing the morbidity and mortality associated with this arrhythmia and in planning the treatment. In this study, we investigated the value of atrial electromechanical delay (AEMD) in predicting the development of PoAF. Methods: A total of 93 patients who underwent isolated coronary artery bypass grafting (CABG) operation were included in this prospective study. Patients' demographic characteristics, laboratory parameters, echocardiographic data, and AEMD durations that could be measured by the co‐use of electrocardiography and echocardiography were recorded. The patients at sinus rhythm during the postoperative period were identified as "Group 1", and those who developed PoAF were identified as "Group 2". Results: PoAF incidence was 26.88% ( n = 25). Left ventricle (LV) lateral AEMD, LV medial AEMD, right ventricle lateral AEMD, and left atrium (LA) lateral AEMD durations of Group 2 were significantly higher than Group 1 ( p < 0.001, p = 0.004, p = 0.004, p < 0.001; respectively). In Univariate Logistic Regression Analysis, the age, hypertension, LA maximum volume, LA lateral AEMD and pulmonary artery pressure were significantly associated with PoAF development ( p = 0.01, p = 0.004, p = 0.004, p = 0.001, p = 0.01; respectively). However, only LA lateral AEMD was found as an independent predictive factor for the development of PoAF in the Multivariate Logistic Regression Analysis (OR:1.03, 95% CI:1.001–1.06, p = 0.04). AUC was .741 for LA lateral AEMD in ROC Curve Analysis (95% CI: .633–.849, p < 0.001). Conclusions: The development of PoAF can be predicted by AEMD durations measured in the preoperative period in patients undergoing isolated CABG.